SKILL-BASED LANGUAGE TEACHING APPROACH: LISTENING, SPEAKING, READING AND WRITING - Muniskhon Sayfiddinova Fahriddin kizi (Western European Studies, 2024)
Skill-based language teaching has emerged as a cornerstone of modern language pedagogy, emphasizing the development of listening, speaking, reading, and writing as essential components of communicative competence. This article explores the theoretical foundations of this approach, detailing its relevance in fostering comprehensive language skills. It provides practical strategies for teaching each skill, addresses common challenges, and highlights the benefits of integrating these skills in a cohesive instructional framework. The findings underscore the need for balanced skill development to achieve linguistic proficiency, offering recommendations for effective implementation in diverse educational contexts.
Keywords: Skill-based teaching; language pedagogy; listening; speaking